A contextual analysis of public health implications of water choices and hygiene practices in Northern Ghana. Issue 5 (4th May 2021) - Jeil, Emmanuel Bintaayi; Abass, Kabila
ABSTRACT: Households' choices of water for domestic and economic purposes and associated hygiene practices have implications for their health. However, scant documentation exists on this, particularly in the Ghanaian context. Using a mixed-methods cross-sectional research design, we conducted interviews with 86 household heads or their representatives (both male and female) to explore the factors that influence water choices, hygiene practices, and public health implications in Northern Ghana. Findings suggest that water choices among participants were influenced mainly by ease of access, availability, and traditional belief systems rather than safety reasons. While the study households drew water mainly from traditional sources including wells, ponds, and streams, socio-cultural practices such as burying the dead near wells make these water sources unsafe. This poses potential health risks to residents. To achieve the Sustainable Development Goal on water, sanitation and hygiene, the Tatale-Sanguli District Assembly should step up efforts in providing potable water and also educate residents against the obsolete and health-endangering socio-cultural practices such as burying the dead near wells.